Safety and effectiveness of paravertebral block for simple mastectomy: a prospective study - Hannan, Mohammad Abdul; Arin, Kazi Mahzabin; Karmakar, Chandra Shekhar; Tusher, Saiful Mahmud; Das, Rajat Shuvra; Sultana, Ayesha (International Journal of Research in Medical Sciences, 2024)
Background: Paravertebral block (PVB) has emerged as an alternative to general anesthesia (GA) for various surgical procedures, offering potential advantages such as improved postoperative pain control and reduced systemic side effects. Simple mastectomy, a common surgical intervention for breast cancer treatment, involves the removal of breast tissue without axillary lymph node dissection. Methods: This prospective study was conducted at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from 1st January 2022 to 30th June 2023. A total of 50 patients undergoing simple mastectomy were randomly assigned. Results: PVB significantly reduced postoperative VAS scores at 1 hour (2.3±1.1 vs. 4.7±1.3), 6 hours (2.1±0.9 vs. 4.4±1.2), 12 hours (1.9±0.8 vs. 3.8±1.0), and 24 hours (1.7±0.6 vs. 3.5±0.9) (all p<0.001). Opioid consumption was lower in the PVB group (4.8±2.1 mg vs. 12.4±3.2 mg, p<0.001). Incidence of PONV was reduced (16% vs. 48%, p=0.019), hospital stay was shorter (2.3±0.5 days vs. 3.1±0.7 days, p=0.001), and patient satisfaction was higher (4.6±0.5 vs. 3.8±0.7, p=0.003). No significant differences were observed in intraoperative hemodynamic parameters or adverse events. Conclusions: Paravertebral block provides superior pain management, reduces opioid use and PONV, shortens hospital stays, and improves patient satisfaction compared to GA in simple mastectomy, demonstrating its efficacy and safety in perioperative care.